Effect of Replanting Zinnia Plants for Remediation of Oil-Contaminated Soil - Mita, Makoto; Ikeura, Hiromi; Kai, Takamitsu; Tamaki, Masahiko (E3S Web of Conferences, 2018)
Previously, we demonstrated that the zinnia plant was effective for the phytoremediation of oil-contaminated soils and that it had a higher remediation effect during the initial growth period. Therefore, repeated planting of zinnia for the initial growth period might enhance the remediation of contaminated soils, so we performed the following study. Seeds were sown in soils containing 4% (w/w) diesel oil and grown for 100 days. We carried out two treatments: replanted plots where above-ground parts of plants were cut after 50 days, and new seeds were sown; or non-replanted plots where plants were allowed to grow for 100 days. The soil dehydrogenase activity and soil total petroleum hydrocarbon concentrations were analyzed. At the end of the study, no significant differences were found between replanted and non-replanted plots for either measurement. Therefore, replanting did not affect remediation. Degradable oil components in the soils may have been degraded in the initial growth period of the first planting, but by the time of replanting there may have been few degradable oil components left in the soil, so there was no beneficial effect of replanting. We concluded that replanting is unsuitable for phytoremediation of oil-contaminated soils.